Combined soil preparation machine of plowing and crop boundaries for smallholder agriculture / Lutfil Hadi Suhaimie, Ab Aziz Mohd Yusof and Kamariah Md Isa - Suhaimie, Lutfil Hadi; Mohd Yusof, Ab Aziz; Md Isa, Kamariah (School of Mechanical Engineering, 2023)
The project is called a combined soil preparation machine of plowing and crop boundaries in agriculture for farmers. The main objectives of this project are to fabricate a physical prototype of the machine that can plow with the alternative blades and to design and improve a machine model that can use a rake and shovel while making crop boundaries. By replacement of the blade, farming can be more efficient because it only uses one machine. The project was started by designing the machine using Solidworks before proceeding with structural analysis to see the strength of the proposed design. The fabrication then proceeded to fabricate the component using measuring, cutting, grinding, and welding. The blade has two alternatives which are rake-type and shovel-type blades. The rural area with poor conditions is the target for this project. This project aims to make a machine cheaper than other available products and has a multi-tasking purpose. The project is trusted to help small farmers farm more efficiently. To conclude, the project’s performance needs to be achieved by the fabrication process and material applied in this project.